Clinical Efficacy of Bone Reconstruction Surgery with Frozen Cortical Bone Allografts for Nonunion of Radial and Ulnar Fractures in Toy Breed Dogs - Munakata, Shuntaro; Nagahiro, Yukari; Katori, Daichi; Muroi, Norihiro; Akagi, Hiroyuki; Kanno, Nobuo; Harada, Yasuji; Yamaguchi, Shinya; Hayashi, Kei; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective To evaluate the effectiveness of frozen cortical bone allografts (FCBA) in the treatment of severe radial and ulnar atrophic nonunion fractures.Animals Toy breed dogs with nonunion of radial and ulnar fractures (n = 15).Methods Severe atrophic nonunion fractures were treated with FCBA (eight infected and seven non-infected fractures). Radiographs obtained immediately after surgery, and 1, 2, 3, 6 and 12 months later were evaluated and scored for the periosteal reaction at the bone regeneration sites, the healing process in the bone connection areas at both the proximal and distal sites, and the bone remodelling process within the allografts.Results Improvements in the fracture-healing process and weight-bearing function were observed in all cases. Radiographic scores at the bone connection areas and within the allograft improved significantly over time (p < 0.05). There were not any significant differences in radiographic scores between the infected and non-infected groups.Clinical Significance Bone reconstruction with FCBA is effective in the treatment of radial and ulnar nonunion fractures associated with large bone defects, regardless of the infection status of the surgical site.
Keywords: frozen cortical bone allograft; radius; nonunion fracture; radiographic analysis; bone infection; surgical treatment